Terceirização e terceirizados no setor bancário: relações de emprego, condições de trabalho e ação sindical - Sanches, Ana Tércia (2006)
This dissertation deals with the processes of outsourcing in the banking sector from the 90's to 2002, as part of the processes of productive reorganization. These processes mean that new forms of production administration and managing the work force have been created and they have changed both working relationships and working conditions for those who work for contracted out companies. This study intends to show that contracted out workers, although part of the bank production system, are not actually part of the banks. The expansion of the automation and the innovations in information technology facilitated the implementation of the processes of outsourcing in paper check clearing process and the bank's back office operations. Contracted out workers do not have workers' rights and are not protected by employment legislation. These changes demand rethinking of union dynamics as they pose new challenges to trade union officers because they directly interfere with the organization and representation of contracted out workers